The prospects of complementary treatment using Red Piper betle (Piper crocatum) against leucorrhoea: an empirical study - Siswina, Tessa; Kurnia, Dikdik; Rustama, Mia Miranti; Sumiarsa, Dadan (Universitas Aisyiyah Yogyakarta, 2023)
One of the main issues for women in the reproductive age range is leucorrhoea, which causes a woman ongoing distress, and occasionally be the first sign of several of the main gynecological disorders. The widespread use of fluconazole antibiotics has caused Candida sp to become resistant. Alternative non-pharmacological treatments based on natural products are needed, especially P. crocatum which has antioxidant, antifungal, and anti-inflammatory activities. This study analyzed the empirical study of P. crocatum used against leucorrhoea due to C. albicans. The empirical study presented that vaginal discharge was reduced after using P. crocatum formulations. The infection parameter of vaginal pH level, the intensity of pain, and itching were significantly recovered with p values of 0.008, 0.000, and 0.001, respectively, while the reducing C. albicans colonies was 0.001. P. crocatum decoction formulation is effective in reducing vaginal yeast infections in women, close to the results of the positive control, ketoconazole.